Assessment of left ventricular function in pediatric oncology by two different methods of echocardiography: a short-term outcome - Shahzad, Muhammad; Luhana, Sujata; Mehtab, Madiha; Mirza, Sadiq; Haque, Anwarul (International Journal of Contemporary Pediatrics, 2022)
Background: Chemotherapy-induced myocardial dysfunction (CIMD) is a documented actuate of heightened morbidity and mortality. The gold standard for the surveillance of CIMD is the serial echocardiogram. Two-dimensional speckle echocardiography i.e. global longitudinal strain (GLS) is affirmative diagnostic tool than conventional echocardiography. Methods: We retrospectively reviewed the data of children (age between 6 months to 18 years) who received cardio-toxic chemotherapeutic agents and underwent echocardiography assessment with conventional and GLS imaging at-least 2 times between January 2020 to January 2021 in The Indus Hospital, Karachi at start, 3rd months and 6th months of treatment. Results: We enrolled 122 patients in our study. The mean age was 8.19±4.43. 82 (67.2%) children got the 2 echocardiographic evaluations while 40 (32.8%) children completed three. Of 82 subjects, 17 (22.6%) had a significant reduction in early myocardial deformation indices as measured by two-dimensional (2D) STE using GLS at the end of 3 months of chemotherapy. Before the start of therapy, mean values of ejection fraction (EF), fractional shortening (FS) and GLS were 68.6±10.44, 38.8±7.44, and -20.7±4.19 respectively. At 3rd month and 6th month follow up, EF decreased 65.80±9.00 and 62.06±10.62 (p value 0.000) respectively while the values for GLS decreased significantly as -18.4±3.86, -16.68±3.63 (p value 0.02) respectively. Conclusions: GLS is an effective, and non-invasive cardiac imaging modality than a conventional echocardiography in assessment of left ventricular (LV) dysfunction in non-symptomatic as well as in symptomatic children with cancers.